Maintenance Strategies, Periodic Renovations and Building Modernisation in the Aspect of the Criterion of the Whole Life Costs - Przesmycka, Apolonia; Wieczorek, Damian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the issues of building exploitation and maintenance and focuses on the characteristics of the maintenance strategies mentioned in the ISO 15686-5:2017 Buildings and constructed assets - Service life planning - Part 5: Life-cycle costing. The article describes all three strategies recommended by the ISO standard (preventive, corrective and deferred maintenance). The purpose of the article is to conduct whole life costs analysis of three variants of modernisations, renovations and maintenance strategies for a selected building. The methods of economic efficiency assessment were used, such as net present value (NPV) method and internal rate of return (IRR) method.
Keywords: maintenance strategies; periodical repaires; building modernization; life cycles; whole life costs; net present value; internal rate of return; plany konserwacji; remonty okresowe; modernizacja budynku; koszt utrzymania obiektu; cykl życia obiektu